PENERAPAN PRINSIP EKONOMI ISLAM PADA PRODUKSI AIR MINERAL ( Studi Kasus CV. Anugrah Pratama DNK Probolinggo ) - ahmad Muhammad al maghrobi; Lukmanul hakim; Salman Al farisi; Reza hilmy luayyin (Wasīlah: Journal Of Sharia Sciences, 2025)
This study aims to examine the application of Islamic economic principles in the mineral water production process. There are three main pillars that are the focus of this study, namely tauhid (belief in the oneness of Allah), maslahah (public interest), and justice. Amidst the growing awareness of the importance of ethical and sustainable business practices, the sharia-based production model offers a relevant framework that is not only oriented towards material profit, but also towards the benefit of all parties.The primary objective of this research is to identify the extent to which these principles are integrated throughout the entire mineral water production chain, from the selection of water sources that must be maintained for sustainability, production processes that prioritize quality and cleanliness, to product distribution that ensures fair access for consumers. Furthermore, this study also aims to analyze how the application of these principles can add value to companies, not only in terms of reputation and consumer trust but also in creating positive social and environmental impacts.The analysis results indicate that the integration of Islamic economic principles in mineral water production has significant potential to form a holistic and sustainable business model. This implementation can serve as a guide for other industries to adopt more ethical and socially responsible business practices, in line with Islamic values.